2003
DOI: 10.1007/s00705-003-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

Genistein, a protein tyrosine kinase inhibitor, suppresses the fusogenicity of Moloney murine leukemia virus envelope protein in XC cells

Abstract: XC cells are highly susceptible to syncytium formation by infection of ecotropic murine leukemia viruses (MLVs) and by expression of their envelope protein (Env). By this property, XC cells are widely used to determine titers of ecotropic MLVs. Number of plaques resulted from the syncytium formation in XC cells by ecotropic MLV infection is corresponding to number of the viral particles. XC cells had been established from a v-src-induced rat tumor. It has been reported that transformed cells are more sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…A review of the current literature has indicated that flavonoids affect virus binding to cell membranes, entry into the cell, replication, viral protein translation within the host cell, and formation of certain glycoprotein complexes of the virus envelope [8]. At the host cell level, isoflavones, mainly genistein but not daidzein, can affect the induction of certain transcription factors and secretion of cytokines; most of these effects have been attributed to a reduction in protein tyrosine kinase activity [18]. Kae and its derivatives have been tested for their potential antiviral properties including reducing herpes simplex virus-1 and poliovirus infection at 0.4 mM and <10 µM, respectively [19], [20].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the current literature has indicated that flavonoids affect virus binding to cell membranes, entry into the cell, replication, viral protein translation within the host cell, and formation of certain glycoprotein complexes of the virus envelope [8]. At the host cell level, isoflavones, mainly genistein but not daidzein, can affect the induction of certain transcription factors and secretion of cytokines; most of these effects have been attributed to a reduction in protein tyrosine kinase activity [18]. Kae and its derivatives have been tested for their potential antiviral properties including reducing herpes simplex virus-1 and poliovirus infection at 0.4 mM and <10 µM, respectively [19], [20].…”
Section: Discussionmentioning
confidence: 99%
“…This result allows us to make a functional differentiation between these two poxviruses at the level of entry into cancer cells. The role of isoflavones like genistein at inhibiting the replication of many distinct viruses has been well documented, ranging from virus binding, (Andres et al, 2007; Hayashi et al, 1997) and entry (Kubo et al, 2003; Li et al, 2000; Sharma-Walia et al, 2004) to virus replication (Evers et al, 2005; Kim et al, 2006; Robin et al, 2001; Yura et al, 1993), viral protein translation, as well as the formation of viral glycoproteins complexes (Andres et al, 2007). Here we show that the kinase targets for genistein are required at very different levels for VACV (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, including genistein, reduced the infectivity of nonenveloped viruses, including the following: single-stranded RNA poliovirus, coxsackie virus and echovirus from the Picornaviridae family [44,50,[55][56][57][58]; double-stranded RNA viruses such as rotavirus [59] and double-stranded DNA viruses including adenovirus [33,34]; and John Cunningham (JC) virus [48] and simian virus 40 (SV40) [54] from the Adenoviridae and Polyomaviridae (JC and SV40) families ( Table 1). Flavonoids also inhibited the infectivity of a variety of enveloped viruses such as single-stranded RNA viruses in the Reoviridae, Arenaviridae, Flaviviridae, Coronaviridae, Ret-roviridae [both human immunodeficiency virus (HIV) and Moloney murine leukemia virus (MoMLV)], Arteriviridae and Paramyxoviridae families, including arenavirus [35], bovine viral diarrhea virus [37], coronavirus [38], HIV [47], MoMLV [49], porcine reproductive and respiratory syndrome (PRRS) virus [51] and respiratory syncytial virus [52]; and double-stranded DNA viruses, including bovine herpes virus (BHV) [36], Epstein-Barr virus (EBV) [39], herpes simplex virus (HSV) 1 [34,40,41,44] and HSV-2 [41], herpes human virus (HHV) 8 [46] and human cytomegalovirus (CMV) [45,60] from the Herpesviridae family.…”
Section: Antiviral Activity Of Isoflavonesmentioning
confidence: 99%